2010
DOI: 10.1111/j.1745-3992.2010.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Think Aloud Protocols for Examining and Confirming Sources of Differential Item Functioning Identified by Expert Reviews

Abstract: This paper demonstrates and discusses the use of think aloud protocols (TAPs) as an approach for examining and confirming sources of differential item functioning (DIF). The TAPs are used to investigate to what extent surface characteristics of the items that are identified by expert reviews as sources of DIF are supported by empirical evidence from examinee thinking processes in the English and French versions of a Canadian national assessment. In this research, the TAPs confirmed sources of DIF identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 32 publications
2
47
0
10
Order By: Relevance
“…This information provided indirect data (or clues) concerning the students' cognitive processes (e.g., what factors may have affected their answering; cf. [11]), thereby making it possible to make more informed guesses about the sources of DIF. The latter document also revealed whether any language-related explanations were suggested by the reviewer for the poor functioning of the items.…”
Section: Methodmentioning
confidence: 99%
See 2 more Smart Citations
“…This information provided indirect data (or clues) concerning the students' cognitive processes (e.g., what factors may have affected their answering; cf. [11]), thereby making it possible to make more informed guesses about the sources of DIF. The latter document also revealed whether any language-related explanations were suggested by the reviewer for the poor functioning of the items.…”
Section: Methodmentioning
confidence: 99%
“…For example, it has been detected that reviewers have frequently been unable to correctly predict DIF and the direction of DIF (e.g., [14][15][16]). Ercikan et al [11] found that reviewers' judgments as to which items are biased and why are frequently incorrect and, therefore, need to be verified by checking them against what the testees themselves think.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of identifying sources of DIF in English and French versions of a Canadian assessment, think-aloud protocols have been proposed recently as a new approach (Ercikan et al, 2010). These researchers examined whether examinees' think-aloud protocols confirmed the linguistic differences identified by expert reviewers as sources of DIF.…”
Section: Sources Of Differential Item Functioningmentioning
confidence: 99%
“…Expert (or judgmental) review -reviews of items by individuals who are knowledgeable about student learning and may have cultural or linguistic expertise -is the most common method for identifying properties of test items (e.g., content, format, context, language) that may cause DIF. However, expert reviews tend to be based on surface characteristics of items (e.g., Ercikan et al, 2010); whether these surface characteristics are the sources of DIF remains an empirical question. Therefore, even though expert reviews can identify whether certain aspects of test items are associated with DIF, they may not identify real sources of DIF.…”
Section: Introductionmentioning
confidence: 99%